Caged polycyclic polyprenylated acylphloroglucinols as Cav3.2 low voltage-gated Ca2+ channel inhibitors from Hypericum curvisepalum. Issue 94 (9th November 2022) - Ye, Yan-Song; Liu, Rui; Jiang, Na-Na; Li, Song-Yu; Nian, Yin; Xu, Gang
Abstract : Caged PPAPs including an unprecedented octahydro-2, 5-methanoindene skeleton were discovered as potent Cav 3.2 T-type Ca 2+ channel inhibitors. Abstract : Five caged polycyclic polyprenylated acylphloroglucinols including an unprecedented octahydro-2, 5-methanoindene skeleton (1 ) were discovered from Hypericum curvisepalum . Biologically, 1 and 2 are potent Cav 3.2 T-type Ca 2+ channel inhibitors with negligible effect on the cardiovascular antitarget, the human ether-à-go-go-related gene potassium channel. Additionally, 2 indicates strong antinociception in the mouse acetic acid writhing test.